2020
DOI: 10.12688/f1000research.25570.2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of stretching exercises on human gait: a systematic review and meta-analysis

Abstract: Background: Stretching is commonly used in physical therapy as a rehabilitation tool to improve range of motion and motor function. However, is stretching an efficient method to improve gait, and if so, for which patient category? Methods: A systematic review of randomized and non-randomized controlled trials with meta-analysis was conducted using relevant databases. Every patient category and every type of stretching programs were included without multicomponent programs. Data were meta-analysed where possibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 82 publications
(170 reference statements)
0
2
1
1
Order By: Relevance
“…It has been hypothesized that strength improvements can improve gait speed through biomechanical factors, with the strength of the hip extensors and ankle plantar flexors acting as the best predictors of gait speed improvement [56]. However, there is no clear evidence of the effect of stretching on gait performance in older adults [57]. Also, in the current study, an unexpected relationship between upper-body strength and flexibility with multiple gait parameters was found.…”
Section: Discussioncontrasting
confidence: 54%
“…It has been hypothesized that strength improvements can improve gait speed through biomechanical factors, with the strength of the hip extensors and ankle plantar flexors acting as the best predictors of gait speed improvement [56]. However, there is no clear evidence of the effect of stretching on gait performance in older adults [57]. Also, in the current study, an unexpected relationship between upper-body strength and flexibility with multiple gait parameters was found.…”
Section: Discussioncontrasting
confidence: 54%
“…Thus, MT can be considered a complementary approach to maintain or improve ROM. However, a recent systematic review showed that no strong level of evidence supports the beneficial effect of using stretching alone to improve gait outcomes despite some scattered results [ 68 ]. These findings are in line with the current research, suggesting that MT alone may not be sufficient to increase ROM during gait as only isolated improvements were identified.…”
Section: Discussionmentioning
confidence: 99%
“…The present study adds to the growing efforts made by researchers to improve APA associated with GI in PD patients by the means of non-pharmacological/non-invasive devices such as powered ankle orthosis ( Petrucci et al, 2019 ), self-triggered stimulus lowering stance side support surface, vibrations applied beneath the stance-side support surface ( Creath et al, 2013 ), whole-body vibration ( Fischer et al, 2019 ), lateral pull applied to the pelvis by motor-driven robotic system ( Mille et al, 2007 ) or rhythmic auditory stimulus ( Ghai et al, 2018 ). Study from our laboratory (not published) further suggests that acute ankle stretching may also be efficient to reduce ankle stiffness and improve APA in this population (see Vialleron et al, 2020 for a review on the effect of stretching on gait). Because gait and balance problems often respond poorly to treatment with anti-parkinsonian medications, and to other interventions such as deep brain stimulation ( Bonnet et al, 1987 ; Krack et al, 2003 ), it is admitted that physical therapy interventions are an important clinical treatment for individuals with PD.…”
Section: Discussionmentioning
confidence: 99%